In vitro spore germination and early gametophyte development of Cibotium barometz (L.) J. Sm. in different media - Yupi ISNAINI; Titien Ngatinem Praptosuwiryo (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Isnaini Y, Praptosuwiryo TNg. 2020. In vitro spore germination and early gametophyte development of Cibotium barometz (L.) J. Sm. in different media. Biodiversitas 21: 5373-5381. Cibotium barometz (L.) J. Sm. is known as the golden chicken fern and included in Appendix II of CITES. It is an important export commodity for traditional and modern medicine. Globally, populations of this species are under significant pressure due to overexploitation in the wild. In vitro culture is one of the technologies used for ex-situ propagation and conservation of rare and endangered ferns and lycophytes. This study’s objectives were: (i) to observe in vitro spore germination and early gametophyte development of C. barometz, and (ii) to determine the best culture medium for rapid spore germination and early development of the gametophytes. The sterilized spores were sown in half-strength Murashige & Skoog (½MS) basal medium supplemented with combinations of 6-Benzylaminopurine (BAP) and ?-Naphthalene acetic acid (NAA). A factorial combination of four BAP concentrations (0, 2, 4, and 6 mg L-1) with four concentrations of NAA (0; 0.01; 0.03 and 0.05 mg L-1) created 16 treatments replicated in a Completely Randomized Design. Spore germination of C. barometz was observed to be Vittaria-type, and its prothallial development was Drynaria-type. Spore germination started 7-14 days after sowing. Young heart-shape gametophytes consisting of 110-240 cells were formed in 45-61 days after sowing. The two best spore culture media for rapid spore germination and development of C. barometz gametophytes were ½ MS with or without 2 mg L-1 BAP.